Peptide TFP5/TP5 derived from Cdk5 activator P35 provides neuroprotection in the MPTP model of Parkinson’s disease - Binukumar, BK. (Mol Biol Cell, 2015)
Parkinson’s disease (PD) is a chronic neurodegenerative disorder characterized by the loss of dopamine neurons in the substantia nigra, decreased striatal dopamine levels, and consequent extrapyramidal motor dysfunction. Recent evidence indicates that cyclin-dependent kinase 5 (Cdk5) is inappropriately activated in several neurodegenerative conditions, including PD. To date, strategies to specifically inhibit Cdk5 hyperactivity have not been successful without affecting normal Cdk5 activity. Previously we reported that TFP5 peptide has neuroprotective effects in animal models of Alzheimer’s disease. Here we show that TFP5/TP5 selective inhibition of Cdk5/p25 hyperactivation in vivo and in vitro rescues nigrostriatal dopaminergic neurodegeneration induced by 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP/MPP+) in a mouse model of PD. TP5 peptide treatment also blocked dopamine depletion in the striatum and improved gait dysfunction after MPTP administration. The neuroprotective effect of TFP5/TP5 peptide is also associated with marked reduction in neuroinflammation and apoptosis. Here we show selective inhibition of Cdk5/p25 hyperactivation by TFP5/TP5 peptide, which identifies the kinase as a potential therapeutic target to reduce neurodegeneration in Parkinson’s disease.